Impacts of Different Membrane Module Designs in Anaerobic Submerged Membrane Bioreactors - Aslan, Mustafa; Saatci, Yusuf (Wiley-Blackwell, 2014)
In this study, the anaerobic submerged membrane bioreactors (AnSMBR) was designed to use in different membrane modules. Furthermore, their treatment performance was investigated. Water quality parameters such as chemical oxygen demand (COD), total organic carbon (TOC), suspended solids, alkalinity, and volatile fatty acids were analyzed. Total system performance was examined by determining biogas generation and composition. The permeate flux and membrane total fouling resistances were measured and efficiencies in AnSMBR system were identified. TOC and COD removal efficiencies did not change in the different membrane modules. However, in sulfate removal rate the cylinder module was more effective compared to other modules. The biogas production is higher in AnSMBRs compared to conventional anaerobic systems. Methane production was determined as 0.35-0.38 L CH4/g CODremoved. When transmembrane pressure was set at 170 +/- 3 mbar, the flux of permeates decreased through the whole operation of the AnSMBR system. The efficiency rank is a cylinder, funnel-shaped and U-shaped module, as membrane modules were compared in terms of providing high permeates fluxes.
Keywords: Biogas generation; Membrane resistance; Permeate flux; Wastewater treatment